The use of alternative double number lines as models of ratio tasks and as models for ratio relations and scaling - Küchemann, Dietmar; Hodgen, Jeremy; Brown, Margaret (2014)
In this paper we draw on ICCAMS project materials that used the double number line (DNL) to develop secondary school students’ understanding of multiplicative reasoning. In particular, we look at the use of a DNL, and its alternative version, as a model of ratio tasks, as a model for developing an understanding of ratio relations, and finally (but only briefly) as a model for developing the notion of multiplication as scaling.